Optimization of constitutive model parameters for simulation of polystyrene concrete subjected to impact. Issue 2 (June 2018) - Yoo, Tae Kwang; Qiu, Tong
This article presents the results of a series of experimental testing and numerical modeling studies to optimize the parameters of a constitutive material model to accurately simulate the behavior of polystyrene crushable concrete during impact loading using LS-DYNA. Quasi-static compression tests and confined drop impact tests were conducted. To model the quasi-static compression tests, the response surface methodology was used to optimize Poisson's ratio and friction angle in the pseudo-tensor model in LS-DYNA. Using the optimized model parameters, the simulated compression stress versus strain relationship showed an excellent agreement with those from the compression tests. To model the confined drop impact tests, the strain rate sensitivity parameter in LS-DYNA was optimized by comparing the drop impact simulations at different strain rate sensitivity values with the drop impact tests. This study suggests that the pseudo-tensor material model is potentially suitable for modeling crushable concrete. Although the optimized constitutive model parameters are specific for the polystyrene concrete mix used in this study, similar approach can be used to optimize model parameters for other polystyrene concrete mixes.